The use of adverbials in the verbal usage of Malay ESL learners at the tertiary level - Wan Adnan, Wan Nur Asyura; Lotfie, Maskanah Mohammad (2014)
In the process of learning a second language, it is suggested that there is a standard developmental trajectory of every linguistic feature that L2 learners follow. Although L2 learners experience common stages in their process of acquisition, the rate of attainment in the process is different. In Malaysian ESL context, the local students at the tertiary institutions have gone through a minimum of eleven years of formal education of English at their primary and secondary level. These 11 years of English language learning process practically should have produced many proficient English language users, however, that is not often the case in Malaysia especially among the Malay learners. All registered students at the public tertiary institutions (except IIUM) are required to enroll in English language proficiency courses because it is learned that the tertiary level students have inadequate English language proficiency. Focusing on adverbials, this study emphasizes the developmental perspective by comparing the elementary and intermediate students’ oral production to see the extent to which Malay ESL learners have developed their use of adverbials after eleven years of English language learning. For data collection purpose, a picture-cued task was administered on 60 Malay ESL students in which they were required to elicit each process in each picture. The result indicated that, in terms of their use of adverbials, most of the Malay ESL students from both proficiency levels are considered to have reached stage 6 of Processability Theory developmental stages and only a number of elementary level students were found to have only reached Level 2. The findings suggest that the ESL practitioners should follow the developmental routes suggested by Processability theory in teaching grammar components to students.